Policy Conflict: A Conflict Analysis of the Relocation Policy of Street Vendors in Simpang Lima, Pati Regency - Walinegoro, Bhakti Gusti; Fitriyono, Junaidul (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2022)
This study aims to analyse the conflicts that stemmed from the relocation of street vendors in Simpang Lima, Pati Regency. This conflict is distinct because it is not only related to the refusal to relocate and improve facility quality, but also local government policies that failed to comprehensively address the problem, thereby wasting time and funds. This qualitative research adapts the Policy Conflict Framework (PCF) to analyse data collected through interviews and literature studies. It thus applies the latest and most appropriate framework for comprehensively analysing policy conflicts, particularly those related to the power relations between stakeholders. In so doing, it finds that relocation resulted from a regulatory mandate that was based on considerations made by the government when carrying out public governance. However, this policy created conflicts due to problems with its content and processes. The conflict in this study is evidence that involved actors’ willingness to compromise is one important factor in reducing conflict intensity.